Marriage Markets and Single Motherhood in South Africa - Siv Gustafsson; Seble Y. Worku (Tinbergen Institute, 2006)
This paper studies the effects of local marriage markets on South African women's marital decisions. The analysis is motivated by the low proportion of married among African mothers since 48% are never married. This means that the children of all these never married mothers have no access to their fathers' resources. The low sex ratio of 92 men to 100 women among Africans aged 20-40 makes us believe that shortage of marriageable men may explain marriage patterns. Economic theory predicts less attractive marital outcomes for women when the sex ratio is low. We analyze this hypothesis using the 2001 Census of South Africa. An ordered probit model is fitted with the different marital type ranked from less desirable (never married) to more attractive (married civil). The estimation results suggest that both the quantity and quality of marriageable men matter in the marital choice of women who have at least one child. Exposing African women to the White woman's marriage market and the achievement of educational levels similar to those of Whites increase their probability of marriage by 8%, implying that only 44% of African women are expected to marry even given good marital opportunities and improved levels of education.
Keywords: D1; J1; 330; local marriage market; sex ratio; marriageable men; ordered probit; African; White